2004
DOI: 10.1179/oeh.2004.10.3.296
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Modified Cotton and Farmers' Health in China

Abstract: This study provides the first evidence of a direct link between the adoption of a genetically modified (GM) crop and improvements in human health. Estimation of the impact of Bacillus thuringiensis (Bt) cotton adoption on pesticide use from data from a survey of cotton farmers in northern China, 1999-2001, showed that Bt cotton adoption reduced pesticide use. Assessment of a health-production function showed that predicted pesticide use had a positive impact on poisoning incidence. Taken together, these result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 4 publications
7
59
1
Order By: Relevance
“…However, as can be seen, the incidence is significantly lower on Bt plots, which is plausible given the lower use of chemical pesticides. This is consistent with research in China, India, and South Africa (Hossain et al, 2004(Hossain et al, , 2003Kouser and Qaim, 2011;Bennett et al, 2003). Fig.…”
Section: Fig 2 About Heresupporting
confidence: 79%
See 1 more Smart Citation
“…However, as can be seen, the incidence is significantly lower on Bt plots, which is plausible given the lower use of chemical pesticides. This is consistent with research in China, India, and South Africa (Hossain et al, 2004(Hossain et al, , 2003Kouser and Qaim, 2011;Bennett et al, 2003). Fig.…”
Section: Fig 2 About Heresupporting
confidence: 79%
“…The existing research concentrates on agronomic and financial impacts of Bt cotton. A few studies have also analyzed reductions in the incidence of acute pesticide poisoning among farmers, due to lower exposure to chemical pesticides (Bennett et al, 2003;Hossain et al, 2004;Kouser and Qaim, 2011). But these effects were not monetized, 1 1 The only study that attempted some economic valuation of the health benefits of Bt cotton adoption is by Kouser and Qaim (2011), using a cost-of-illness approach.…”
Section: Introductionmentioning
confidence: 99%
“…Estimation results are shown in Table 4. The regression results showed that pesticide use affected not only the magnitude of these indicators (Table 3), but also the normal function of nervous and hematological systems, as shown in Table 4 5) . Similar to the impact on the magnitudes of these indicators, the impact on abnormal readings of nervous system and hematological system was also detected only when pesticides were sprayed within 24 h.…”
Section: Resultsmentioning
confidence: 99%
“…By 2012, GM crop areas reached 170 million hectares, benefiting dozens of millions of farmers [3]. While previous studies have indicated a reduction in acute (visible) pesticide poisoning in farmers because of GM crops [4,5], the impact of this reduction on farmers' long-or short-term invisible health has not been quantitatively analyzed.…”
mentioning
confidence: 99%
“…There is, however, no published evidence that Bt-cotton has resulted in a general change in the pest spectrum leading to an overall increase of pesticide applications. In addition to direct environmental benefits, pesticide reductions related to the adoption of Bt-cotton have also shown to have reduced many immediate as well as longer-term risks to human health [163][164][165][166].…”
Section: Pesticide Reductions Due To Insect-resistant Cropsmentioning
confidence: 99%